Navigasi Karier di Era Digital: Menemukan Passion dan Peluang untuk Remaja - Dachmiati, Sabrina; Sahin, Arif; Hesta, Ogy Yan; Nur’aini, Desi; Wibowo, Bagas Hari (Universitas Pahlawan Tuanku Tambusai, 2025)
Advances in science and technology, especially in the era of Industry 4.0, have encouraged individuals to actively compete in the job market. This community service program aims to empower prospective counseling mentors in the Oshibana NaraArt Bekasi Community through workshops focused on developing career adaptation skills. The implementation method consists of four stages: planning, community education, dissemination of science and technology, and training. The results of the activity show that 90% of participants actively participated in the entire workshop series, with 85% successfully developing career narratives that include identifying individual strengths and adaptation plans for technological disruption. Additionally, participants reported an increased understanding of the importance of career flexibility and digital skills. The program also successfully formed a working group for ongoing career mentoring and designed a career guidance module based on Lift Design. As such, this initiative is expected to make a positive contribution to the development of skills and career readiness among youth, as well as strengthen the support network for prospective mentors in providing effective guidance.